1977
DOI: 10.1002/1097-0142(197709)40:3<1052::aid-cncr2820400313>3.0.co;2-g
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of lung cancer by radiotherapy, chemotherapy, and methanol extraction residue of BCG (MER).Clinical and immunological studies

Abstract: Fifty-one patients with advanced lung cancer were divided at random into two groups. One group of 29 patients received the methanol extraction residue (MER) of Bacille-Calmette-Guerin (BCG) in addition to radiotherapy and/or chemotherapy. The other group of 22 patients was treated by radiotherapy and/or chemotherapy alone. The immune status of the patients was evaluated by skin tests to three recall antigens and KLH and by in vitro lymphocyte stimulation to PHA and three recall antigens. The immune status of b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

1977
1977
1984
1984

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…Also in our study lymphocyte transformation was evaluated by the morphology of the cells rather than by measuring the incorporation of [3H]thymidine. However, there are reports by others who did not find depressed lymphocyte transformation in lung cancer patients (Silk, 1967;Sutherland et al, 1971;Robinson et al, 1977;Barnes et al, 1975).…”
Section: Discussionmentioning
confidence: 87%
“…Also in our study lymphocyte transformation was evaluated by the morphology of the cells rather than by measuring the incorporation of [3H]thymidine. However, there are reports by others who did not find depressed lymphocyte transformation in lung cancer patients (Silk, 1967;Sutherland et al, 1971;Robinson et al, 1977;Barnes et al, 1975).…”
Section: Discussionmentioning
confidence: 87%
“…MER is a methanol extraction residue of BCG organisms killed by phenol and washed with acetone which has immunostimulatory properties (Weiss, 1972). It has been used recently for non-specific immunotherapy in cancer patients with beneficial effect on the cutaneous reactivity and on the in-vitro lymphocyte transformation responses (Robinson et al, 1975;1977).…”
mentioning
confidence: 99%
“…MER has been found to be a potent immunostimulator when given i.d. (Robinson et al, 1975(Robinson et al, , 1977 but has never been'given i.v. If MER could be administered i.v.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, we have reported that i.d. injection of MER improved skin reactivity and the lymphocyte in vitro response to various antigens (Robinson et al, 1975(Robinson et al, , 1977. In the present study we have evaluated tolerance to i.v.…”
mentioning
confidence: 98%